2019
DOI: 10.3390/v11110979
|View full text |Cite
|
Sign up to set email alerts
|

Viral Metagenomics Revealed Sendai Virus and Coronavirus Infection of Malayan Pangolins (Manis javanica)

Abstract: Pangolins are endangered animals in urgent need of protection. Identifying and cataloguing the viruses carried by pangolins is a logical approach to evaluate the range of potential pathogens and help with conservation. This study provides insight into viral communities of Malayan Pangolins (Manis javanica) as well as the molecular epidemiology of dominant pathogenic viruses between Malayan Pangolin and other hosts. A total of 62,508 de novo assembled contigs were constructed, and a BLAST search revealed 3600 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
405
2
19

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 359 publications
(430 citation statements)
references
References 52 publications
4
405
2
19
Order By: Relevance
“…Such a case has been proposed for Malayan pangolins (Liu et al 2019), a meat delicacy that was most likely sold in the exotic meat market. It has been proposed, though not yet proven, that 2019_nCoV naturally propagates in bats, but the bat species in which the population mainly resides was unknown at the time of writing.…”
Section: Resultsmentioning
confidence: 99%
“…Such a case has been proposed for Malayan pangolins (Liu et al 2019), a meat delicacy that was most likely sold in the exotic meat market. It has been proposed, though not yet proven, that 2019_nCoV naturally propagates in bats, but the bat species in which the population mainly resides was unknown at the time of writing.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, Paulo Eduardo Brandão, a virologist from the University of St. Paul, also said, "There is no evidence that snakes can be infected by this new coronavirus and act as hosts" [34]. A study on the genome sequence of diseased pangolins smuggled from Malaysia to China found that pangolins carry coronavirus, suggesting that pangolins may be intermediate hosts for SARS-COV-2 [35]. Pangolins seized in anti-smuggling operations in Guangxi and Guangdong of southern China were detected with multiple CoV linages with 85.5-92.4% genome sequence similarity to those of SARS-CoV-2 [36].…”
Section: Intermediate Hostsmentioning
confidence: 99%
“…Although humans and bats live in different environments, some wildlife species are susceptible to the novel coronaviruses in nature, highlighting that the need of tracing its origin of 2019 human coronavirus in wild animals. Previously, researchers had demonstrated that coronaviruses had been detected in pangolins [6]. Here, we explore the phylogenic relationship of the human SARS-CoV-2 together with pangolin-and bat-origin coronaviruses.…”
mentioning
confidence: 94%